Strategies to Increase Customer Purchase Intention of an E-Commerce Platform - Dipa Mulia (Dinasti International Journal of Digital Business Management, 2025)
This study examines strategies to increase purchase intention on e-commerce platforms in Indonesia, with a specific focus on the under-explored role of governance. The research examines the direct and indirect effects (mediated by trust) of e-service quality, customer reviews, governance, and trust on purchase intention. Using a quantitative approach, data were collected from 200 Indonesian e-commerce consumers via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that governance, e-service quality, and trust have significant direct effects on purchase intention. However, trust fully mediates only the relationship between customer reviews and purchase intention, and does not act as a mediator for e-service quality or governance. The findings suggest that to enhance purchase intention, platform managers should prioritize improving both governance mechanisms and e-service quality directly, while also leveraging customer reviews to build consumer trust.